Opinions of Future Teachers on Training in Social Sciences Didactics - Felices-De la Fuente, María del Mar; Chaparro-Sainz, Álvaro (Frontiers in Education, 2021)
At present, an understanding of the teaching practices at university and the opinion of students about these practices is limited, at least in certain knowledge areas. Given this diagnosis and in the context of Social Sciences Didactics, we consider it important to analyze teaching practices and how they impact future teachers. Consequently, concerned about the quality of training offered to students, this study aims to know their opinion about which teaching practices they consider most appropriate to train in Social Sciences Didactics, once they finish the subjects related to this area. To this end, a non-experimental quantitative design has been used, involving collecting information through a questionnaire completed by 875 students from seven Spanish universities studying for the Degree in Primary Education. The data was analyzed from a triple perspective, an analysis of the descriptive statistics of the items contemplated in this research, the existing correlations between them, and a statistical analysis based on the gender variable. The results show that the treatment of controversial issues and the didactic outings outside the university classroom are the strategies most valued by the students in teaching specific content of the subject Social Sciences Didactics. The results also show significant differences in the responses to each item depending on the gender variable. We conclude that students widely value university teaching practices related to implementing active methodologies, analyzing current social and environmental issues, and collaborative work dynamics. Likewise, it is observed that women have, on the whole, a better opinion than men regarding these types of methodologies and strategies.